KINEMATIČKA ANALIZA APERKATA BOKSERA REPREZENTATIVNOG NIVOA - Izet Kahrović; Oliver Radenković; Rifat Mujanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Technique of blows in boxing is very difficult to learn because it requires a high level of coordination of the entire body. Movement to perform right uppercut in the head is quite complex. In performance of uppercust, it is very pronounced extensions in knee joint with plantar flexion in the upper parts of the feet, hocks, while somewhat less pronounced body rotation around the longitudinal axis. The subject of this research is kinematic analysis of boxers uppercuts representative level. The problems of research are speed and angles of elbow joint uppercuts of boxers representative level. The aim was to determine differences in hand speed and angles of the elbow joint. The task was to:capture shocks, preparing images for digitization, digitization and processing of data in the software HUMAN. Sample of examiners are representative level two boxers. The subjects performed upperacts, and the material is captured by the ca- 346 CRNOGORSKA SPORTSKA AKADEMIJA, "Sport Mont" časopis br. 31,32,33. mera Casio FX speed 300 frames per second. Video record is processing in software HUMAN, digitizing 3-point, two-segment models of the human body. Analyze the speed of the reference points of the hand, elbow and shoulder, and angle of the elbow joint. Large differences were observed between the speed of the shoulder and elbow joints, and hands occasionally performing uppercust in both subjects as well as the obvious differences in rates centers shoulder joints, elbow and hand and compared subjects with each other, which was the objective of the study. The observed differences in the angle between forearm and upper arm with two boxers in all three phases of shock, do not differ greatly from the most favorable angles to perform this technique.